2022
DOI: 10.3390/ijms23169010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Behavior of Perivascular Cells (Pericytes and CD34+ Stromal Cell/Telocytes) in Sprouting and Intussusceptive Angiogenesis

Abstract: Perivascular cells in the pericytic microvasculature, pericytes and CD34+ stromal cells/telocytes (CD34+SCs/TCs), have an important role in angiogenesis. We compare the behavior of these cells depending on whether the growth of endothelial cells (ECs) from the pre-existing microvasculature is toward the interstitium with vascular bud and neovessel formation (sprouting angiogenesis) or toward the vascular lumen with intravascular pillar development and vessel division (intussusceptive angiogenesis). Detachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 213 publications
2
9
0
Order By: Relevance
“…The characteristics and distribution of the CD34+SCs/TCs around apparently unaffected skin vessels and appendages in early KS lesions agree with those previously described in several conditions [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], creating microenvironments within the tissues (a contribution to maintenance and modulation of local homeostasis) [ 21 , 31 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Likewise, the ability of CD34+SCs/TCs to envelop perivascular inflammatory infiltrates in KS is also consistent with their role in retaining and modulating the immune cells [ 31 , 53 , 54 , 55 , 56 , 57 ], allowing us to explain the presence of an inflammatory component around some intussusceptive pre-existing blood vessels within neovessels (vessels into vessels: a promontory sign in KS).…”
Section: Discussionsupporting
confidence: 54%
“…The characteristics and distribution of the CD34+SCs/TCs around apparently unaffected skin vessels and appendages in early KS lesions agree with those previously described in several conditions [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], creating microenvironments within the tissues (a contribution to maintenance and modulation of local homeostasis) [ 21 , 31 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Likewise, the ability of CD34+SCs/TCs to envelop perivascular inflammatory infiltrates in KS is also consistent with their role in retaining and modulating the immune cells [ 31 , 53 , 54 , 55 , 56 , 57 ], allowing us to explain the presence of an inflammatory component around some intussusceptive pre-existing blood vessels within neovessels (vessels into vessels: a promontory sign in KS).…”
Section: Discussionsupporting
confidence: 54%
“…67 Recent reports showed that tubal TCs are indirectly involved in local angiogenesis, particularly the CD34 + TCs subtype. 68 These TCs dissociated from their perivascular niche, formed a composite structure with fibrin and fibronectin, proliferated and differentiated to be stromal cells during granulation tissue formation. 69 Additionally, TCs also express measurable quantities of pro-angiogenic microR-NAs (let-7e, 10a, 21, 27b, 100, 126-3p, 130a, 143, 155 and 503).…”
Section: Tcs and Sprouting Angiogenesismentioning
confidence: 99%
“…Several studies found that TCs could inhibit microvascular endothelial cell apoptosis and promote angiogenesis in myocardial infarction and in chronic inflammation of the uterus and ovaries, such as uterine myoma 67 . Recent reports showed that tubal TCs are indirectly involved in local angiogenesis, particularly the CD34 + TCs subtype 68 . These TCs dissociated from their perivascular niche, formed a composite structure with fibrin and fibronectin, proliferated and differentiated to be stromal cells during granulation tissue formation 69 .…”
Section: Roles Of Tcs Mediated Cell Communication In Pulmonary Fibros...mentioning
confidence: 99%
“…Additionally, pericytes can differentiate into non-mesenchymal cells, such as neurons. Notably, pericytes derived from skeletal muscle have been reported to differentiate into the high class Ⅲ beta-tubulin (Tuj-1) expressing neurons [39] .…”
Section: Biological Functions Of the Pericytesmentioning
confidence: 99%